MATERIALISE THIRDSPACE THROUGH SOCIO-SPATIAL INTEGRATION (Cases of Study: Thamrin 10, Jalan H. Agus Salim, Jalan Percetakan Negara, and Jalan Kramat Raya) - Yohannes Basuki Dwisusanto; Ruth Dea Juwita (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2022)
Urban informality is a phenomenon of everyday life in Jakarta but has not been extensively discussed, especially in spatial design practice. Previous study shows that informal space in the city is shaped by economic activities and urban opportunities heavily influence the flow of urbanisation in Indonesia. The study aims to examine the materialisation of Thirdspace through the forms of socio-spatial integration using Henri Lefebvre’s Production of Space (1991) and Edward Soja’s Thirdspace (2010). The use of theory connects the case study with other bodies of work in architecture that are looking to develop understandings of how spatial, social, and other urban contexts might be challenged and intertwined in urban informality. Using their respective body of work, the study is conducted in the four selected objects of study: Thamrin 10, Jalan H. Agus Salim, Jalan Percetakan Negara, and Jalan Kramat Raya. The findings reveal that the concrete abstraction of Thirdspace emerges in everyday life through urban informality, materialised by informal actors. The materialisation of Thirdspace is possible due to (1) participation of informal actors, (2) space occupied by informal actors, and (3) activities conducted by informal actors. As abstraction will become true in practice, socio-spatial integration of urban informality is an abstraction that becomes true through social and spatial practice.